Clinical utility of tensiomyography for muscle function analysis in athletes - García-García O; Cuba-Dorado A; Álvarez-Yates T; Carballo-López J; Iglesias-Caamaño M (Dove Medical Press, 2019)
Oscar García-García, Alba Cuba-Dorado, Tania Álvarez-Yates, Javier Carballo-López, Mario Iglesias-CaamañoLaboratory of Sports Performance, Physical Condition and Wellness, Faculty of Education and Sport Sciences, University of Vigo, Pontevedra, SpainAbstract: An exhaustive review has been made to filter the studies that have analyzed muscle function though tensiomyography (TMG) with elite or well-trained athletes. The results of this review indicate that the several protocols used in athletes to find the displacement-time curve with greater maximum radial muscle displacement showed a good-excellent reliability. TMG has been used to characterize athletes’ muscles contractile properties from specific sports disciplines, although there are very few sports that have been deeply analyzed. TMG seems to be useful to determine changes in muscles contractile properties after stimuli of competition, training or recovery. These changes have been strongly related with the fatigue produced after an effort. In addition, TMG parameters could be used to control training effects during a specific period or throughout the season being also a very useful tool to individualize athletes training loads. In this sense, it also seems to provide sports performance information in cyclic sports by relating some TMG parameters with performance indicators. On the other hand, the TMG-BCM algorithm has been used as a lateral and functional symmetry measure and as a monitoring tool for injury prevention and recovery. However, it seems to be no clear criterion that determines asymmetry degree, nor established contractile properties values as a reference to prevent or recover sports injuries. Despite the utility shown in these fields, there are still very few sports analyzed and it is really necessary to continue advancing in the knowledge of the contractile properties behavior, such as the effects of athletes’ training, competitions and injuries and even in the parameters interpretation obtained with the TMG.Keywords: TMG, contractile properties, elite athletes, neuromuscular parameters, muscle assessment, muscle response